Functional traits of lianas in an Australian lowland rainforest align with post‐disturbance rather than dry season advantage. (12th May 2019) - Buckton, Genevieve; Cheesman, Alexander W.; Munksgaard, Niels C.; Wurster, Chris M.; Liddell, Michael J.; Cernusak, Lucas A.
Abstract: Lianas are an important component of tropical forests; they alter tree mortality and recruitment and impact biogeochemical cycling. Recent evidence suggests that the abundance of lianas in tropical forests is increasing. To understand and predict the effect of lianas on ecosystem processes in tropical forests, it is important to understand the mechanisms through which they compete with trees. In this study, we investigated the functional traits of lianas and trees in a lowland tropical forest in northeast Queensland, Australia. The site is located at 16.1° south latitude and experiences significant seasonality in rainfall, with pronounced wet and dry seasons. It is also subject to relatively frequent disturbance by cyclones. We asked the question of whether the canopy liana community at this site would display functional traits consistent with a competitive advantage over trees in response to disturbance, or in response to dry season water stress. We found that traits that we considered indicative of a dry season advantage (xylem water δ 18 O as an indicator of rooting depth; leaf and stem tissue δ 13 C and instantaneous gas exchange as measures of water‐use efficiency) did not differ between canopy lianas and canopy trees. On the other hand, lianas differed from trees in traits that should confer an advantage in response to disturbance (low wood density; low leaf dry matter content; high leaf N concentration; high mass‐based photosynthetic rates). We conclude that the liana community at the study site expressed functional traits geared towards rapid resource acquisition and growth in response to disturbance, rather than outcompeting trees during periods of water stress. These results contribute to a body of literature which will be useful for parameterising a liana functional type in ecosystem models.